2020
DOI: 10.1186/s40510-019-0303-z
|View full text |Cite
|
Sign up to set email alerts
|

Pain level between clear aligners and fixed appliances: a systematic review

Abstract: Objectives: To assess if there is any difference in pain levels between orthodontic treatment with clear aligners or fixed appliances. Materials and methods: An electronic search was completed in PubMed, The Cochrane Database, Web of Science, Scopus, Lilacs, Google Scholar, Clinical Trials, and OpenGrey databases without any restrictions until February 2019. All comparative study types contrasting pain levels between clear aligners and fixed appliances were included. The risk of bias (RoB) was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 53 publications
3
51
0
15
Order By: Relevance
“…Deformation of aligners has been reported as the primary cause of this pain and discomfort 13 . The results of the available studies are generally in agreement with each other, suggesting that CAT causes slightly less pain and discomfort than fixed appliances during the first few days of treatment, whilst differences seem to be negligible later in treatment 15 …”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Deformation of aligners has been reported as the primary cause of this pain and discomfort 13 . The results of the available studies are generally in agreement with each other, suggesting that CAT causes slightly less pain and discomfort than fixed appliances during the first few days of treatment, whilst differences seem to be negligible later in treatment 15 …”
Section: Introductionsupporting
confidence: 61%
“…Orthodontic pain associated with clear aligner therapy (CAT) has been investigated in several studies. CAT appears to follow an analogous pattern of pain progression compared to fixed orthodontic appliances in terms of peaking at 24 hours and trending towards baseline levels after 7 days 12‐15 . Deformation of aligners has been reported as the primary cause of this pain and discomfort 13 .…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In this context, previous studies reported positive changes and high satisfaction with Invisalign treatment especially with eating, chewing and appearance 19,36,37 . Invisalign treatment was associated with better satisfaction, better oral health related quality of life, and less negative impacts on oral health than fixed orthodontics [12][13][14][15][16]19,20,37,38 . They were associated with less disruption to eating and chewing and were rated as more satisfactory than fixed appliances 16 .…”
Section: Discussionmentioning
confidence: 92%